Systematic KMTNet Planetary Anomaly Search. II. Six New q < 2 × 10−4 Mass-ratio Planets - Hwang K-H; Zang W; Gould A; Udalski A; Bond IA; Yang H; Mao S; Albrow MD; Chung S-J; Han C; Jung YK; Ryu Y-H; et al. (IOP Publishing on behalf of the American Astronomical Society, 2022)
We apply the automated AnomalyFinder algorithm of Paper I to 2018-2019 light curves from the ≃13 deg2 covered by the six KMTNet prime fields, with cadences Γ ≥ 2 hr-1. We find a total of 11 planets with mass ratios q < 2 × 10-4, including 6 newly discovered planets, 1 planet that was reported in Paper I, and recovery of 4 previously discovered planets. One of the new planets, OGLE-2018-BLG-0977Lb, is in a planetary caustic event, while the other five (OGLE-2018-BLG-0506Lb, OGLE-2018-BLG-0516Lb, OGLE-2019-BLG-1492Lb, KMT-2019-BLG-0253, and KMT-2019-BLG-0953) are revealed by a "dip"in the light curve as the source crosses the host-planet axis on the opposite side of the planet. These subtle signals were missed in previous by-eye searches. The planet-host separations (scaled to the Einstein radius), s, and planet-host mass ratios, q, are, respectively, (s, q × 105) = (0.88, 4.1), (0.96 ± 0.10, 8.3), (0.94 ± 0.07, 13), (0.97 ± 0.07, 18), (0.97 ± 0.04, 4.1), and (0.74, 18), where the "± "indicates a discrete degeneracy. The 11 planets are spread out over the range . Together with the two planets previously reported with q ∼ 10-5 from the 2018-2019 nonprime KMT fields, this result suggests that planets toward the bottom of this mass-ratio range may be more common than previously believed.
Keywords: Gravitational microlensing exoplanet detection (2147)